2015
DOI: 10.5365/wpsar.2015.6.2.003
|View full text |Cite
|
Sign up to set email alerts
|

Global Handwashing Day 2012: a qualitative content analysis of Chinese social media reaction to a health promotion event

Abstract: Our study showed that social media and traditional media are two interconnected arms of the GHD campaign in China. Our analysis demonstrated that public health campaigns in China can be evaluated using social media data. The themes and topics identified in this study will help public health practitioners evaluate future social media handwashing promotion campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The HKSAR stated that "PPPs provide a number of alternative ways involving the private sector in delivery of public services and the health financing system by systemically analyzing the effectiveness and sustainability of seven PPP initiatives carried out in the HKSAR." [4][5][6][7][8][9][10][11] For instance, the implementation of the General Outpatient Clinic and Elderly Health Care Voucher programs has been recognized as a useful strategy for organizing care by public not-for-profit nongovernmental organizations (NGOs) and charitable organizations, which successfully extended the private sector's complementary role in the public sector. Hemodialysis and cataract PPPs provide opportunities for forprofit corporations to build their profile for market expansion.…”
Section: Current Understanding and Application Of Ppps In China's Hmentioning
confidence: 99%
“…The HKSAR stated that "PPPs provide a number of alternative ways involving the private sector in delivery of public services and the health financing system by systemically analyzing the effectiveness and sustainability of seven PPP initiatives carried out in the HKSAR." [4][5][6][7][8][9][10][11] For instance, the implementation of the General Outpatient Clinic and Elderly Health Care Voucher programs has been recognized as a useful strategy for organizing care by public not-for-profit nongovernmental organizations (NGOs) and charitable organizations, which successfully extended the private sector's complementary role in the public sector. Hemodialysis and cataract PPPs provide opportunities for forprofit corporations to build their profile for market expansion.…”
Section: Current Understanding and Application Of Ppps In China's Hmentioning
confidence: 99%
“…Other studies have pointed to the importance of improving the use of social media platforms by IPC professionals in order to leverage the latest technologies in conveying hand hygiene messages [43,49,50]. This was further illustrated in a study conducted in China, which suggested that hand hygiene promotion strategies could be assessed using information obtained from social media, augmenting the data provided by traditional sources such as radio, print, and television [51]. According to the study performed by Pan et al [50], a hand hygiene campaign video was more effectively connected through Facebook than through a group email and hospital website in Taiwan.…”
Section: The Example Of Hand Hygienementioning
confidence: 99%
“…Conversely, a loss-framed message is persuasive in promoting mammography, chest self-examination [ 30 ], and colorectal cancer detection [ 31 ]. Given the prior research [ 15 ] and the text-based message expression of Weibo [ 32 ], we posit that the gain-framed and loss-framed effects on health-promoting message dissemination on Weibo are similar to those of print media. A Weibo message that clearly expresses positive or negative consequences was regarded as framed.…”
Section: Introductionmentioning
confidence: 99%